IMPLEMENTASI LITERASI BUDAYA SISWA UNTUK MENGEMBANGKAN KETERAMPILAN SOSIAL - Nawir, Muhammad; Septianingsih, Septianingsih; Dwiyasta, Vanezal; Ramadhani, Rahma; Sukri, Justika (STKIP Persada Khatulistiwa Sintang, 2025)
Cultural literacy refers to the understanding of values, norms, and cultural practices that form part of social life. In the educational context, cultural literacy plays an important role in shaping students’ character, particularly in developing social skills. This study aims to describe the implementation of cultural literacy within the school environment and its contribution to the development of students’ social skills. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The results indicate that activities such as reading folktales, illustrating local cultural symbols, presenting one’s own and others’ cultures, effectively foster social skills including cooperation, respect, and empathy. The study concludes that cultural literacy can serve as an effective strategy for strengthening character education and enhancing students’ social skills in the school setting.